Dynamics of following and leading: association of movement synchrony and depression severity - Jennissen, Simone; Sandmeir, Anna; Schoenherr, Desiree; Altmann, Uwe; Nikendei, Christoph; Schauenburg, Henning; Friederich, Hans-Christoph; Dinger, Ulrike (Frontiers in Psychiatry, 2024)
Objective: Depression negatively affects interpersonal functioning and influences nonverbal behavior. Interpersonal theories of depression suggest that depressed individuals engage in behaviors that initially provoke others' support and reassurance, but eventually lead to rejection that may also be expressed nonverbally.This study investigated movement synchrony as a nonverbal indicator of support and rejection and its association with depression severity in a sample of depressed and healthy individuals. Semi-standardized diagnostic interview segments with N = 114 dyads were video recorded. Body movement was analyzed using Motion Energy Analysis, synchrony intervals were identified by computing windowed cross-lagged correlations. Depression severity was assessed via both self-rating (BDI-II) and clinician rating (HAMD).Results: Both self-rated and clinician-rated depression severity were negatively correlated with patient-led, but not clinician-led movement synchrony measures. The more hat formatiert: Hochgestellt hat gelöscht: 35 depressed patients were, the less they initiated movement synchrony with their clinicians. These correlations remained significant after controlling for gender, age, gross body movement, and psychopharmacological medication.Findings suggest that depression may negatively affect patients' active initiative in interaction situations. Automatized methods as used in this study can add valuable information in the diagnosis of depression and the assessment of associated social impairments.